Identification of QTLs and candidate genes screening for hypoxia tolerance in Pacific white shrimp (Litopenaeus vannamei) - Xiawen Li; Yian Zhu; Zhixiang Yuan; Cunyu Duan; Yu Chen; Lei Yang; Minghui Ye; Wei Wang; Zhongduo Wang; Huapu Chen; Yulei Zhang; Changxu Tian (Aquaculture Reports)
The Pacific white shrimp (Litopenaeus vannamei, also known as Peneaus vannamei) is pivotal in global aquaculture, with its growth and survival significantly influenced by hypoxia conditions in farming. This study aimed to uncover the genetic basis of hypoxia tolerance to enhance farming efficiency and sustainability. We evaluated hypoxia tolerance in a shrimp mapping family and identified quantitative trait loci (QTLs) and candidate genes associated with this trait. The F1 full-sibling family exhibited significant variation in hypoxia tolerance, with an average survival time of 13 hours at dissolved oxygen levels of 0.4 mg/L. Whole-genome sequencing of 200 offspring and their parents generated 81,892 markers for a genetic map with 44 linkage groups over 5386.79 cM. The linkage group lengths ranged from 12.79 cM to 196.86 cM, averaging 122.43 cM, with marker distances from 0.03 to 0.61 cM and highest and lowest marker densities observed in LG11 and LG44, respectively. QTL analysis revealed 8 QTLs associated with hypoxia tolerance, encompassing 78 annotated genes, 13 of which were identified as candidate genes for hypoxia tolerance. RNA-seq analysis of hypoxia-tolerant and hypoxia-intolerant individuals revealed 1973 differentially expressed genes, with GO and KEGG enrichment analyses highlighting their roles in DNA repair, RNA processing, and redox-related pathways. Integrating QTL and RNA-seq data pinpointed 11 genes with differential expression under hypoxic stress. This study not only advances the understanding of the genetic mechanisms underlying hypoxia tolerance in L. vannamei but also establishes a foundation for enhancing hypoxia resilience through genetic improvement.